Responsabilidade civil: a existência de um mercado de danos morais e as decisões de “mero aborrecimento" - Marchese, Pâmela (2022)
In a society with difficult dialogue, where conflicts tend to end up in the judiciary, analyzing the suitability of indemnity claims is essential. The term “moral damages industry” has been known for some time, however, this research goes further, and seeks to analyze the aspect of commodification present in the term. The research was structured in an exploratory way and has as a theoretical reference the concept of moral damages by civilist scholars such as Tartuce, Nader and Schreiber. The study raises hypotheses about the professional ethics of lawyers and the abuse of the right of action by the petitioners, when supported by the gratuitousness of justice. The problematization seeks to understand the reasons for the excess of indemnity claims for moral damages which, in the end, are considered “mere annoyance”.